Comparison of sport-specific and non-specific exercise testing in inline speed skating - Stangier, C.; Abel, T.; Mierau, J.; Gutmann, B.; Hollmann, W.; Struder, H. K. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The most effective way to measure exercise performance in inline speed skating (ISS) has yet to be established. Generally most athletes are examined by means of traditional but unspecific cycling (CYC) or running (RUN) testing. The present study investigates whether a sport-specific incremental test in ISS reveals different results.